Convergence of Eigenvalues and Eigenfunctions of Nonlinear Dirichlet Problems in Domains with Fine-Grain Boundary - Namleeva, Yu. V.; Skrypnik, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We study the behavior of eigenvalues and eigenfunctions of the Dirichlet problem for nonlinear elliptic second-order equations in domains with fine-grain boundary.